The Impact of Free Strategy and Delivery Speed on Consumer Satisfaction with the Level of Ease of Product Return as a Moderation Variable on Shopee Marketplace Users in DKI Jakarta - Yulianti, Yulianti; Lukiyana, Lukiyana; Suryono, Imam (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of free shipping strategy and delivery speed on consumer satisfaction with the level of ease of product returns as a moderation variable for Shopee marketplace users in DKI Jakarta. The approach used is through a quantitative approach and the Partial Least Square (PLS) method, data was collected from 153 respondents. The results of the study show that free shipping, delivery speed, and ease of product returns have a positive and significant effect on consumer satisfaction. However, the variable of ease of return of products actually weakens the relationship between free shipping and satisfaction, and does not moderate the relationship between delivery speed and consumer satisfaction significantly. These findings emphasize the importance of aligning promotional strategies and after-sales service in improving consumer satisfaction in the e-commerce sector. This research makes a practical contribution for marketplace managers in designing services that are more responsive to customer needs.